2011
DOI: 10.1074/jbc.m110.210120
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Apoptosis by the Immunophilin Aryl Hydrocarbon Receptor-interacting Protein (AIP) Involves Mitochondrial Import of the Survivin Protein

Abstract: Survivin is a multifunctional protein with essential roles in cell division and inhibition of apoptosis, but the molecular underpinnings of its cytoprotective properties are poorly understood. Here we show that homozygous deletion of the aryl hydrocarbon receptor-interacting protein (AIP), a survivin-associated immunophilin, causes embryonic lethality in mice by embryonic day 13.5-14, increased apoptosis of Ter119 ؊ / CD71؊ early erythropoietic progenitors, and loss of survivin expression in its cytosolic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
(105 reference statements)
4
37
1
Order By: Relevance
“…The reported association of AIP with TOMM20 (Yano et al 2003) leaves room to speculate that AIP could stabilise survivin in the cytoplasm and facilitate its displacement into the mitochondria pool, increasing the reserves of survivin in this compartment readily for subsequent events that involve apoptosis (Kang & Altieri 2006). This hypothesis has recently been experimentally confirmed by the same group (Kang et al 2011). However, because several evidences suggest that AIP acts as a tumour suppressor gene (Leontiou et al 2008), it is not clear why it stabilises survivin, thereby elevating the cellular anti-apoptotic threshold.…”
Section: Survivinsupporting
confidence: 54%
See 1 more Smart Citation
“…The reported association of AIP with TOMM20 (Yano et al 2003) leaves room to speculate that AIP could stabilise survivin in the cytoplasm and facilitate its displacement into the mitochondria pool, increasing the reserves of survivin in this compartment readily for subsequent events that involve apoptosis (Kang & Altieri 2006). This hypothesis has recently been experimentally confirmed by the same group (Kang et al 2011). However, because several evidences suggest that AIP acts as a tumour suppressor gene (Leontiou et al 2008), it is not clear why it stabilises survivin, thereby elevating the cellular anti-apoptotic threshold.…”
Section: Survivinsupporting
confidence: 54%
“…2). The fact that AIP is a highly conserved protein could be expected for two reasons: first, because AIP is associated with a human disease, and several studies have found that genes causing human disease are more conserved than non-disease genes (Lovell et al 2009), and secondly, because AIP has been demonstrated to be essential in cardiac development and in maintaining productive erythropoiesis in mice , Kang et al 2011 and previous studies in mammals and other eukaryotes showed that essential genes are usually located in highly conserved genomic regions (Lovell et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among anti-apoptotic factors, the IAP family plays an important cytoprotective function in cancer cells downstream of the intrinsic apoptosis pathway (1518). Therefore, we asked whether the expression of survivin, a member of the IAP family, could be affected by ASK.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that machineries involved in the preprotein import are modified to enhance the mitochondrial transport of Hsp90. This may be associated with the functional modifications of unidentified cytosolic regulatory factors regulating protein trafficking during malignant transformation (41). Post-translational modification, such as phosphorylation, is an important means to regulate the protein function in vivo.…”
Section: Regulation Of Trap1 and Mitochondrial Hsp90mentioning
confidence: 99%